1997
DOI: 10.1177/088307389701200703
|View full text |Cite
|
Sign up to set email alerts
|

"Joubert Syndrome" Revisited: Key Ocular Motor Signs With Magnetic Resonance Imaging Correlation

Abstract: Joubert syndrome is characterized by episodic hyperpnea and apnea, developmental delay, hypotonia, truncal ataxia, ophthalmologic abnormalities, and vermian dysgenesis. We studied 15 patients with the diagnosis of Joubert syndrome to (1) more fully define the syndrome's clinical features, and (2) correlate the clinical features with magnetic resonance imaging (MRI) findings. Eight of 15 patients had a history of episodic hyperpnea and apnea. All patients had developmental delay and hypotonia. Of the 13 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
239
0
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 281 publications
(247 citation statements)
references
References 30 publications
(7 reference statements)
5
239
0
3
Order By: Relevance
“…Joubert syndrome is a severe developmental disorder mainly consisting of ataxia, oculomotor apraxia and mental retardation and characterized by cerebellar vermis hypoplasia and a peculiar brainstem malformation known as the "molar tooth sign" 1,2 . Patients frequently display additional features of cystic kidney disease progressing to renal failure and ocular manifestations including retinopathy, encompassing the Joubert Syndrome Related Disorders (JSRD) group of conditions [3][4][5] .…”
Section: Introductory Paragraphmentioning
confidence: 99%
“…Joubert syndrome is a severe developmental disorder mainly consisting of ataxia, oculomotor apraxia and mental retardation and characterized by cerebellar vermis hypoplasia and a peculiar brainstem malformation known as the "molar tooth sign" 1,2 . Patients frequently display additional features of cystic kidney disease progressing to renal failure and ocular manifestations including retinopathy, encompassing the Joubert Syndrome Related Disorders (JSRD) group of conditions [3][4][5] .…”
Section: Introductory Paragraphmentioning
confidence: 99%
“…Our findings of ocular motor defects are in agreement with the findings of earlier studies. 4,7,9,10 Defects in smooth pursuit and VOR cancellation can be contributed to deformed cerebellar vermis. Saccades and quick phases of nystagmus are generated involving the brainstem.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Diagnostic criteria in JS include hypotonia, ataxia, global developmental delay, and the neuroradiological finding of 'molar tooth sign'. 3,4 The term 'JS-related disorders' was introduced referring to a group of pleiotropic conditions presenting the pathognomonic features of JS associated with variable involvement of other organs and systems. Almost all JS-related disorder genes, so far identified, encode for proteins expressed in the primary cilium or in the centrosome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Steinlin et al 15 reviewing 34 subjects with NPCA found three pairs of siblings but only one child had vermis cerebellar hypoplasia as the only abnormality, since the other siblings had also hemispheres cerebellar hypoplasia or even normal cerebellum. Joubert's syndrome is a rare autosomal recessive condition and the criteria for the diagnosis has been outlined: irregular breathing in the neonatal period, developmental delay, mental retardation, hypotonia, ocular motor abnormalities, and, occasionally, retinal dystrophy and cystic kidneys associated with cerebellar malformation consisting in vermis hypoplasia or agenesis and abnormalities at the pontomesencephalic junction [16][17][18][19] . We describe the clinical and radiological findings of a pair of siblings and compare them with the literature.…”
mentioning
confidence: 99%